1994
DOI: 10.1177/019791839402800107
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Immigration to North America

Abstract: "This article is a comparative study of Brazilian immigration to Canada and the United States. Analysis of recently collected data in Toronto, Ontario and in a medium-size U.S. community facilitated the examination of the adaptation and adjustment experiences of a new group of immigrants to North America. This article begins with a discussion of the origins of this recent immigrant group and its rapid expansion. Next, it focuses on the labor force activities of Brazilian immigrants and compares and contrasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 1 publication
1
26
0
6
Order By: Relevance
“…Significant migration from Brazil to the US is relatively recent. Goza (1994) shows that Brazilian immigration to the US was relatively minor prior to the 1980s (with only slightly more than 50,000 Brazilian‐born individuals in the US at the time of the 1980 US Census). Many of these migrants arrived in the late 1960s and 1970s, after the 1965 Immigration and Naturalization Act opened the doors to migrants from South America.…”
Section: Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant migration from Brazil to the US is relatively recent. Goza (1994) shows that Brazilian immigration to the US was relatively minor prior to the 1980s (with only slightly more than 50,000 Brazilian‐born individuals in the US at the time of the 1980 US Census). Many of these migrants arrived in the late 1960s and 1970s, after the 1965 Immigration and Naturalization Act opened the doors to migrants from South America.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Many of these migrants arrived in the late 1960s and 1970s, after the 1965 Immigration and Naturalization Act opened the doors to migrants from South America. With the onset of the Brazilian economic crisis of the 1980s, however, the number of Brazilian‐born immigrants in the US greatly increased (Goza, 1994; Margolis, 1994, 1998; Sales, 1998; Martes, 2000; Beserra, 2003; Marcus, 2008, 2009). In her study of a Brazilian migrant community in Massachusetts, Sales (1998) found that a majority of her sample arrived in the US between the years 1985 and 1989.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Through the interdisciplinary nature of this study I make several unique contributions. With the exception of the special issue of Ilha do Desterro (2001) and the works on labour by Franklin Goza and his colleagues (Goza 1994(Goza , 1999Goza and DeMaris 2003), Brazilian-Canadian flows have been largely overlooked in the transnationality literature. In English, scholarly work about capoeira is rare although the body is often made central (see Bruhns 2000;Delamont 2005;Downey 2002Downey , 2005Lewis 1995;Stephens and Delamont 2006;Talmon-Chvaicer 2004).…”
mentioning
confidence: 99%
“…Target earners are sojourners aiming for a specific financial goal. Because this usually involves attempting to save as much money as possible, as quickly as possible (Goza, 1994, Margolis, 1994, we expect them to make the transition to an employed state as soon as possible and to have lower reservation wages. The related variable REMIT monitors the effect of sending remittances to Brazil on unemployment duration.…”
Section: Theoretical Considerationsmentioning
confidence: 99%